Development and validation of QMortality risk prediction algorithm to estimate short term risk of death and assess frailty: cohort study - Hippisley-Cox, Julia; Coupland, Carol (BMJ Publishing Group, 2017)
Objectives: To derive and validate a risk prediction equation to estimate the short term risk of death, and to develop a classification method for frailty based on risk of death and risk of unplanned hospital admission.